Structural,optical and electrical characterization of ITO, ITO/Ag and ITO/Ni transparent conductive electrodes - Ali, A.H.; Shuhaimi, A.; Hassan, Z. (Elsevier, 2014)
We report on the transparent conductive oxides (TCO) characteristics based on the indium tin oxides(ITO) and ITO/metal thin layer as an electrode for optoelectronics device applications. ITO, ITO/Ag andITO/Ni were deposited on Si and glass substrate by thermal evaporator and radio frequency (RF) mag-netron sputtering at room temperature. Post deposition annealing was performed on the samples in airat moderate temperature of 500◦C and 600◦C. The structural, optical and electrical properties of theITO and ITO/metal were characterized using X-ray diffraction (XRD), UV–Vis spectrophotometer, Halleffect measurement system and atomic force microscope (AFM). The XRD spectrum reveals significantpolycrystalline peaks of ITO (2 2 2) and Ag (1 1 1) after post annealing process. The post annealing alsoimproves the visible light transmittance and electrical resistivity of the samples. Figure of merit (FOM) ofthe ITO, ITO/Ag and ITO/Ni were determined as 5.5 × 10−3−1, 8.4 × 10−3−1and 3.0 × 10−5−1, respec-tively. The results show that the post annealed ITO with Ag intermediate layer improved the efficiencyof the transparent conductive electrodes (TCE) as compared to the ITO and ITO/Ni.